(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Pharmacology and toxicology is the field of biomedical sciences that cares with the study of medication and the drug action, where a drug can be defined as any chemical substance, that, when taken by a living organism, produces a therapeutic effect and promote well-being. Objective : The Aim of this study was to assess the students’ attitudes toward, perceptions of and feedback surrounding pharmacology and toxicology teaching methods. Method : This was a cross-sectional study involved a survey given to 3rd years and 4th years pharmacy (Pharm D + B Pharm) students and medical students with a total number of (108) participants. The study was administered through a pre-validated questionnaire containing questions based on the internationally accepted “Likert Scale”. Results : The study showed that students favored many changes in pharmacology and toxicology, including the trend of teaching them to third year and fourth year students (48%), instruction on how to choose drugs rationally in future practice (48%), distribution of handouts before lectures (43%), clinical pharmacology (49%), teaching certain topics during pre-final or final year (35%), and a combination of multiple choice questions (MCQs) and written and oral rating evaluation methods for examination (40%). Students were in favour of that pharmacology should be integrated horizontally with other paraclinical subjects and emphasis on problem solving exercises rather than on didactic (teaching) lectures. Conclusion : It is evident that there is an imperative need to implement radical changes in the teaching of pharmacology and toxicology, changes that would allow the pharmacist and/or doctor of tomorrow to render better health services.